PERAN PENGUNGKAPAN EMISI KARBON DAN INOVASI HIJAU PADA NILAI PERUSAHAAN SEKTOR ENERGI TAHUN 2022-2024 - Audrey, Nabila; Lestari, Winda Rika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), 2026)
This study examines the impact of carbon emissions disclosure and green innovation on firm value (proxied by Tobin's Q) for energy companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. The research uses secondary data from annual reports and sustainability reports, with a sample of 12 companies selected by purposive sampling, yielding 36 observations. Data analysis was performed using multiple linear regression in IBM SPSS Statistics 25. The results indicate that carbon emissions disclosure has a negative and significant effect on firm value, meaning that broader disclosure is associated with lower value perception by investors. Meanwhile, green innovation does not have a significant effect, suggesting that green innovation efforts did not noticeably increase firm value during the study period. The Adjusted R Square of 10.2% shows the model’s limited ability to explain variation in firm value. Overall, investors appear to take carbon emissions disclosure into account, whereas green innovation has not yet become a factor that raises firm value within the examined timeframe. Keywords — Carbon Emission Disclosure, Green Innovation, Firm Value, Tobin's Q, Energy Sector.